A review of the human wildlife conflicts around the Nairobi National Park, Kenya - Burudi, Jocelyn; Katona, Krisztián; Tormáné Kovács, Eszter (Review on Agriculture and Rural Development, 2023)
Human-wildlife conflicts are one of the most important challenges facing wildlife conservation. In Kenya, the Nairobi National Park (NNP) experiences various pressures due to its small size and close proximity to an expanding city. The unfenced southern part of the park is the main hotspot for conflicts. For the review a content analysis of 21 publications related to NNP published between 2011 and 2022 was conducted to identify the causes, types and the mitigation measures of conflicts around the park. Documents for the analysis were collected through Google Scholar, Web of Science and Scopus. Our results indicate that livestock predation linked to lions is the major type of conflict superseded by retaliatory killings of the carnivores by the local communities. Other conflicts include crop raids by ungulates and the spread of diseases especially the East Coast fever that is transmitted from the wildebeest to livestock. Findings further reveal that one of the main causes of the conflicts is the expanding human population, which has encroached on wildlife dispersal corridors. It resulted in land subdivision and fencing of the farms as farmers try to protect their livestock from wildlife. This has greatly impeded wildlife migration. Mitigation methods in place include compensation schemes and landowners leasing their farms to the park management so that the corridors can be left open for free wildlife movement. These have however been inadequate therefore there is still a need to find sustainable mitigation measures that ensure coexistence between humans and wildlife in and around NNP.